Germ Cell Tumor with Bronchial Fistula (2020)
Germ cell tumors account for 15% of anterior mediastinum tumors. Fistulas are abnormal communications between two surfaces covered by the epithelium. A fistula can occur between the bronchial tree and the adjacent anatomical structures secondary to variable etiologies. The main clinical manifestations of bronchial fistulas include hemoptysis, purulent cough, and pneumonia, which might threaten the patient's life. Diagnosis can be established with computed tomography, which shows direct and indirect signs of a fistulous tract. We present the case of a 25-year-old patient, with an embryonic carcinoma of the mediastinum, who developed a fistula between the mediastinal mass and the bronchial tree after chemotherapy and thoracic radiotherapy. We carried out a review of the literature about the epidemiological aspects and the physiopathology and the relevant radiological findings of this pathology.